Diagnosis and treatment of uncomplicated type B aortic dissection. (December 2016) - Cooper, Michol; Hicks, Caitlin; Ratchford, Elizabeth V; Salameh, Maya J; Malas, Mahmoud
A type B dissection involves the aorta distal to the subclavian artery, and accounts for 25–40% of aortic dissections. Approximately 75% of these are uncomplicated with no malperfusion or ischemia. Multiple consensus statements recommend thoracic endovascular aortic repair (TEVAR) as the treatment of choice for acute complicated type B aortic dissections, while uncomplicated type B dissections are traditionally treated with medical management alone, including strict blood pressure control, as open repairs have a prohibitively high morbidity of up to 31%. However, with medical treatment alone, the morbidity, including aneurysm degeneration of the affected segment, is 30%, and mortality is 10% over 5 years. For both chronic and acute uncomplicated type B aortic dissections, emerging evidence supports the use of both best medical therapy and TEVAR. This paper reviews the current diagnosis and treatment of uncomplicated type B aortic dissections.